Influence of environmental factors оn children’s dental health - Popovych, З. Б.; Rozhko, М. М. (Actual Dentistry, 2021)
Many studies have identified the negative impact of adverse environmental factors on public health. We studied the influence of chemical production factors on the dental health of children in Ivano-Frankivsk region. The aim of our work was to study the correlation between dental morbidity of the population of Ivano-Frankivsk region and the influence of environmental factors. Material and methods of the study. To study the prevalence of dental diseases, more than 4.9 thousand people of different ages living in the Carpathian region (Ivano-Frankivsk region), in particular in the city of Kalush and Kalush district, which meet the criteria of an “ecological emergency”, were examined, 824 school-age children were examined. The research has been conducted for more than 10 years, and the research work is funded by the Ministry of Health of Ukraine. Results and discussion. As a result of the survey, it was found that the prevalence of dental diseases ranges from 82.2% to 94.3%. Periodontal diseases were diagnosed in 35.3–78.3% of children and adolescents, and a significant number of cases of orthodontic pathology (31.4–43.7%) were observed. In children, the rapid progression of caries was prevalent, often involving multiple caries. When examining children of different ages, many of them (63.7% of all children diagnosed with caries) tended to have an acute course of the carious process. Cheilitis (angular, exfoliative), glossitis (most often desquamative glossitis) were detected in 24.3% of schoolchildren. A combination of several types of pathology was observed. Conclusion. As a result of the study, a correlation was established between the level of dental morbidity in the population and environmental factors, indicating the need for regionally targeted prevention programs.